TEACHER COMPETENCY IN DEVELOPING SOCIAL SCIENCES INSTRUMENTS IN SDIT AL-FITYAN SOMBA OPU DISTRICTS, GOWA DISTRICT - Mirnawati; Nursalam; M. Basri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to describe teachers' ability to determine the supporting and inhibiting factors of teacher competence in the preparation of assessment instruments for social studies subjects. The type of research used is qualitative research through a descriptive approach, with the sample determined by purposive sampling consisting of the principal, teachers in grades III and VI, and students in grades III and VI. This study concluded that teachers who taught already had good pedagogical competencies in the preparation of assessment instruments. Furthermore, the increase in pedagogical competence was supported by several supporting factors, namely: (1) high level of education; (2) participation in various training and scientific activities; (3) length of service and work experience; (4) level of welfare; (5) awareness of obligations and responsibilities; (6) availability of facilities and infrastructure; (7) principal leadership; and (8) guidance activities undertaken. The inhibiting factor for teacher pedagogical competence was the lack of understanding of the 2013 curriculum assessment.